Infection biology of aeciospores of Uromyces viciae-fabae under warm humid conditions - CHAND*, RAMESH; SHROFF, SHARAD; KUSHWAHA, CHANDA; KHARWAR, R.N.; SINGH, A.K. (Indian Phytopathology, 2011)
Germination of aeciospore (9.26 %) was observed on 0.2 % water agar. Germination varied from 5.35 to 6.5% onleaf. Germtube length was reduced upon leaf with increased diameter. Only 1.2 to 1.5 % germinated aeciospores developedappressorium on stomata. Dikaryotic nuclear condition was found both in aeciospores and germtubes. Vesicles like structureswere also found on germtubes. Penetration peg emerged from the vesicle like structures and infected the host throughstomata. After, penetration fungal mycelium aggregated at few places in the mesophyll cells. Morphogenesis was initiated inthe aggregated mycelium after 6 to 8 days of infection. Mycelial cell differentiated in the aecidial initials which subsequentlydeveloped into acediophores and peridial cell. These aecediophores bear aeciospores under the protective cover of peridiallayer. Mature aeciospores released from aecidia by breaking the peridial layer.